War in a time of peace : - Halberstam, David (Touchstone, 2002)
Evoking the internal conflicts, unchecked egos, and power struggles within the White House, the State Department, and the military, Halberstam shows how the decisions of men who served in the Vietnam War, and those who did not, have shaped America's role in global events. He provides fascinating portraits of those in power—Clinton, Bush, Reagan, Kissinger, James Baker, Dick Cheney, Madeleine Albright, and others—to reveal a stunning view of modern political America